1974
DOI: 10.1111/j.1476-5381.1974.tb09676.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Benzoctamine and Chlordiazepoxide on Turnover and Uptake of 5‐hydroxytryptamine in the Brain

Abstract: Benzoctamine, a new psychoactive drug, known to exert in man an anti‐anxiety effect resembling that of chlordiazepoxide, decreased the disappearance of intraventricularly‐injected [14C]‐5‐hydroxytryptamine (5‐HT) from rat brain, as did chlordiazepoxide. Both drugs partially inhibited the α‐ethyl‐3‐hydroxy‐4‐methylphenylethylamine‐induced depletion of rat brain 5‐HT. It is concluded that benzoctamine, like chlordiazepoxide, decreases 5‐HT turnover in the brain and that this action may play a role in the anti‐an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…(1970) reported that diazepam markedly retarded the decline of 14C-5-HT and 14C-5-HIAA in the rat brain; in addition the efflux of intracisternally injected 14C-5-HIAA was retarded. Very similar results were obtained by LIPPMANN and PUGSLEY (1974) and PUGSLEY and LIPPMANN (1975 with 20 mg' kg-I chlordiazepoxide i.p. STEIN et ai.…”
Section: -Hydroxyindoleacetic Acid (5-hiaa)supporting
confidence: 90%
See 1 more Smart Citation
“…(1970) reported that diazepam markedly retarded the decline of 14C-5-HT and 14C-5-HIAA in the rat brain; in addition the efflux of intracisternally injected 14C-5-HIAA was retarded. Very similar results were obtained by LIPPMANN and PUGSLEY (1974) and PUGSLEY and LIPPMANN (1975 with 20 mg' kg-I chlordiazepoxide i.p. STEIN et ai.…”
Section: -Hydroxyindoleacetic Acid (5-hiaa)supporting
confidence: 90%
“…a-Ethyl-3-hydroxy-4-methylphenethylamine (H 75/ 12) is an amine which is selectively taken up into 5-HT neurons and displaces 5-HT. Neither diazepam nor the thienodiazepine, Y-7131, prevented the 5-HT depletion induced by H 75/12 (LIPPMANN and PUGSLEY, 1974).…”
Section: -Hydroxyindoleacetic Acid (5-hiaa)mentioning
confidence: 80%
“…Anthracene and its derivatives constitute an important class of molecules belonging to the family of a polycyclic aromatic compounds, which are widely used in organic synthesis, biological research and in the production of dyes or other materials with interesting photochemical and photophysical properties [1–3] . Notably, the carbocyclic scaffold of anthracene cycloadducts is present in bioactive molecules, especially with antidepressant activity with maprotiline, [4] benzoctamine [4b–5] and oxaprotiline [6] being representative examples of tricyclic antidepressants (TCAs, Figure 1).…”
Section: Figurementioning
confidence: 99%
“…Among the established [4 + 2] cycloaddition reactions, anthracene derivatives are of particular synthetic interest owing to the convenient availability of these feedstocks and the attractive bioactivities of the resulting cycloadducts (e.g., molecules I-IV, Fig. 1B) [60][61][62][63] . In order to break the inherent aromatic stability of anthracene, activated functional groups are typically required to assemble on the anthracene ring (Fig.…”
mentioning
confidence: 99%